IInformacyjne wspomaganie oświaty - Majorek, Bogdan (Wydawnictwo Naukowe UAM w Poznaniu, 1997)
In view of a constant growth of writings on didactic and educational problems it is necessary to create an efficient system of scientific educational information. This system will provide creative teachers with materials that will facilitate the selection and access to materials that will enrich the teachers' methodological base and their own intellectual potential by means of a network of school and pedagogical libraries. Such well-organized and efficiently operating system at the level of the school superintendent's office, whose links will be educational institutions as well as those that improve teaching methods of the teaching staff, may be of great information and practical importance in the present age of rapid transformations. It will become an instrument that will make contact with pedagogical writings and improvement of qualifications of the teaching staff possible.
Keywords: podręcznik konwencjonalny; podręczni elektroniczny; podręcznik audiowizualny; kultura audiowizualna; conventional workbook; electronic workbook; audiovisual workbook; audiovisual culture; Neodidagmata